The-1306C>T Polymorphism in the Promoter Region of matrix metalloproteinase (MMP)-2 Gene in Colorectal Cancer Patients - Anh, Tô Thị Vân; Thảo, Bùi Phương; Hằng, Vũ Thu; Ngọc, Ngô Thị; Phương, Lê Lan; Bích, Phạm Thị; Linh, Nguyễn Thị Tú; Hà, Đỗ Minh; Bình, Phạm Kim; Thái, Trịnh Hồng (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract : The aim of this study was to investigate the relation between -1306C>T polymorphism in promoter region of the MMP-2 gene and the risk of colorectal cancer (CRC) in Vietnamese patients. Tissue samples from 120 CRC patients and blood samples from 60 donors were analyzed in our study using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) and DNA sequencing approach. We found that the incidence of -1306C>T was 13.6% and 21.7 % in the tissue of CRC patients and blood samples of controls, respectively. We further observed a tendency of higher risk of CRC in the patients harboring CC genotype. The CT genotype appeared more frequently in CRC patients with rectal tumor than that in the colon one (P<0.05). Moreover, the prevalence of CT genotype decreased when the size of tumor increased (P<0.05). There were no significant association between the given genotypes and the other pathological parameters (age, gender, differentiation, N, T and TNM stages) in the CRC patients. These findings implied the impact of -1306C>T polymorphism on transcriptional expression of MMP-2 and proposed a potential approach for identification of population with high risk of CRC. Keywords : -1306C>T polymorphism, colorectal cancer, MMP-2, PCR-RFLP.